Effects of Honeybee Venom Acupuncture Therapy on the Poststroke Hemiplegic Shoulder Pain - Yin, Chang-Shik; Nam, Sang-Soo; Kim, Yong-Suk; Lee, Jae-Dong; Kim, Chang-Hwan; Koh, Hyung-Kyun (Korean Pharmacopuncture Institute, 2000)
Hemiplegic shoulder pain(HSP) is one of the most frequent and difficult problems affecting poststroke hemiplegic patients. Honeybee venom acupuncture therapy(BVAT) is known for its pain relieving effects in arthralgia. To evaluate the effectiveness of BVAT on HSP, 24 patients were sequential1y allocated into BVA T treatment group and control group and monitored for 4 weeks at time interval of initial(T0), 1 week(T1), 2 weeks(T2) and 4 weeks(T4). In treatment group, 1:10000 honeybee venom solution 0.2㎖ was injected into acupoint(s) following Deqi three times a week. Kyonu(LI15) was used in the first week. Thereafter Kyonu(LI15) and Nosu(SI10) were used. Visual analogue scale of pain severity showed significant decrease in treatment group compared to control group at T2 and T4 evaluation. Painless passive range of motion of shoulder external rotation showed significant increase in treatment group compared to control group at T4 evaluation. Fugl-Meyer Motor Assessment of upper limb motor function and Modified Ashworth scale of the spasticity of upper limb showed no difference between two groups. BVAT showed as an effective therapy in HSP and further extensive clinical studies are expected.